When medicine transforms art. Issue 4 (2nd July 2019) - Belga, Sara; MacDonald, Clayton; Kabbani, Dima; Roelofs, Kelsey; Hussain, Mohammed Wasif; Cervera, Carlos
Abstract: A 40‐year‐old female with a history of type 1 diabetes mellitus and solitary pancreas transplant, presented with pancreatic graft rejection 1‐year post‐transplant. Incidentally, a 1.1 cm right lower lobe cavity was identified during her workup. Given the augmentation of immunosuppression, voriconazole was empirically started for possible invasive pulmonary aspergillosis. As the patient was a painter, this resulted in a significant change in the colors of her paintings. Ultimately, she was diagnosed with pulmonary coccidioidomycosis and her visual disturbances resolved after the voriconazole was changed to fluconazole. Voriconazole causes visual disturbances in 20%‐30% of the patients most commonly phototopsias; dyschromatopsias typically involving the tritan axis have also been reported. This case illustrates well the potential impact of voriconazole on spectral sensitivity and color perception.